Penerapan Alat Peraga Kartu Huruf Bergambar Untuk Meningkatkan Ketrampilan Menulis Huruf Tegak Bersambung Di Kelas 2 SD Negeri 1 Senon - Unik Setiya Ningrum; Fauzi Fadliansyah (Desanta Publisher, 2024)
This research aims to improve the skills of writing cursive letters in class II students at SD Negeri 1 Senon through the use of picture letter cards. The method used in this research is an experimental method with a one-group pretest-posttest design. The sample for this research was 14 class II students at SD Negeri 1 Senon. Data was collected through a cursive writing test before and after treatment. Data analysis was carried out using the pretest-posttest t test to see the improvement in cursive writing skills after treatment. The results of the study showed that there was a significant increase in the skill of writing cursive letters after using the picture letter card props. In conclusion, the use of picture letter card teaching aids can effectively improve the skills of writing cursive letters in class II students at SD Negeri 1 Senon